Muscle protein metabolism in female swimmers after a combination of resistance and endurance exercise - Tipton, K. D.; Ferrando, A. A.; Williams, B. D.; Wolfe, R. R. (Journal of Applied Physiology, 1996)
There is little known about the responses of muscle protein metabolism in women to exercise. Furthermore, the effect of adding resistance training to an endurance training regimen on net protein anabolism has not been established in either men or women. The purpose of this study was to quantify the acute effects of combined swimming and resistance training on protein metabolism in female swimmers by the direct measurement of muscle protein synthesis and whole body protein degradation. Seven collegiate female swimmers were each studied on four separate occasions with a primed constant infusion of ring-[13C6]phenylalanine (Phe) to measure the fractional synthetic rate (FSR) of the posterior deltoid and whole body protein breakdown. Measurements were made over a 5-h period at rest and after each of three randomly ordered workouts: 1) 4,600 m of intense interval swimming (SW); 2) a whole body resistance-training workout with no swimming on that day (RW); and 3) swimming and resistance training combined (SR). Whole body protein breakdown was similar for all treatments (0.75 +/- 0.04, 0.69 +/- 0.03, 0.69 +/- 0.02, and 0.71 +/- 0.04 mumol.min-1.kg-1 for rest, RW, SW, and SR, respectively). The FSR of the posterior deltoid was significantly greater (P < 0.05) after SR (0.082 +/- 0.015%/h) than at rest (0.045 +/- 0.006%/h). There was no significant difference in the FSR after RW (0.048 +/- 0.004%/h) or SW (0.064 +/- 0.008%/h) from rest or from SR. These data indicate that the combination of swimming and resistance exercise stimulates net muscle protein synthesis above resting levels in female swimmers.